Acetylated tubulin associates with the fifth cytoplasmic domain of Na+/K+-ATPase: possible anchorage site of microtubules to the plasma membrane - Zampar, Guillermo Gaston (2009)
We showed previously that NKA (Na+/K+-ATPase) interacts with acetylated tubulin resulting in inhibition of its catalytic activity. In the present work we determined that membrane-acetylated tubulin, in the presence of detergent, behaves as an entity of discrete molecular mass (320–400 kDa) during molecular exclusion chromatography. We also found that microtubules assembled in vitro are able to bind to NKA when incubated with a detergent-solubilized membrane preparation, and that isolated native microtubules have associated NKA. Furthermore, we determined that CD5 (cytoplasmic domain 5 of NKA) is capable of interacting with acetylated tubulin. Taken together, our results are consistent with the idea that NKA may act as a microtubule–plasma membrane anchorage site through an interaction between acetylated tubulin and CD5.